2011
DOI: 10.1007/s10528-011-9440-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of One Chloroplastic Ascorbate Peroxidase Gene from Nelumbo nucifera

Abstract: A novel ascorbate peroxidase (APX) cDNA was obtained from Nelumbo nucifera (Elian). The phylogenetic analysis indicated that N. nucifera APX grouped together with chloroplastic APX of high plants. The recombinant protein expressed by PET-30a vector showed APX activity (0.04 mM ascorbate min(-1) mg(-1) protein). The APX mRNA was expressed in young leaves, roots, terminal buds, and leafstalks. Synergistic expression of N. nucifera APX and MnSOD mRNA was indicated in the short-term response to mechanical wounding. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Additionally, no thylakoid membrane domain was observed in the COOH terminus and confirmed the localization of APX in the stroma of the chloroplast (Dong et al 2011). ROS (and its reaction products) are regularly produced in the mitochondrial respiratory chain reactions.…”
Section: Localizationsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, no thylakoid membrane domain was observed in the COOH terminus and confirmed the localization of APX in the stroma of the chloroplast (Dong et al 2011). ROS (and its reaction products) are regularly produced in the mitochondrial respiratory chain reactions.…”
Section: Localizationsupporting
confidence: 62%
“…cDNAs isolated from spinach were reported to encode sAPX and tAPX containing common chloroplast transit peptides of 70 amino acid residues (Ishikawa et al 1996). Notably, the amino acid sequences of tAPX and sAPX were found identical except for C-terminal of tAPX, which is the putative transmembrane segment and was 50 amino acids longer than that of sAPX (Dong et al 2011).…”
Section: Localizationmentioning
confidence: 99%
“…APX activity was up-regulated substantially when plants were subjected to environmental stresses, for instance, heavy metals, high salinity, drought, high temperature, and wounding (Shi et al, 2001). APX has been cloned from many plant species such as pea (Mittler and Zilinskas, 1991), Arabidopsis (Kubo et al, 1992;Santos et al, 1996;Maruta et al, 2012), maize (van Breusegem et al, 1995), spinach (Webb and Allen, 1995;Yoshimura et al, 1999), tobacco (Orvar and Ellis, 1995), strawberry (Kim and Chung, 1998), barley (Shi et al, 2001), potato (Kawakami et al, 2002), rice (Lu et al, 2005), Vitis pseudoreticulata (Lin et al, 2006), birch (Wang et al, 2009), muskmelon (Cheng et al, 2009), lily (Chen et al, 2010), grain sorghum (Chen et al, 2011), and Nelumbo nucifera (Dong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al ( 2009 ) observed that in C. melo , the gene expression level of CmAPX varied in different tissues, and with the highest expression in leaves and roots. Chen et al ( 2011 ) found that NuAPX showed higher expression levels in leaf stalks than in root, due to the reasons that the tissues of the leaf stalks and leaf were rich in chloroplast and mitochondria, which was the leading source of reactive oxygen species (ROS) through the electron-transport chain of photosynthesis. In this study, ScAPX6 was constitutively expressed in sugarcane tissues and with the highest expression in pith but the lowest in root (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the orientation characteristic, there are three mainly APX subfamilies in plants, such as cytoplasm APX (cAPX), thylakoid APX (tAPX), and APx-R (Apx-Related) (Mano et al, 1997 ; Shigeoka et al, 2002 ; Chew et al, 2003 ; Dunand et al, 2011 ). APXs gene have been reported in several plants such as Nelumbo nucifera (Chen et al, 2011 ), Hordeum vulgare (Shi et al, 2001 ), Solanum tuberosum (Kawakami et al, 2002 ), Z. mays (Breusegem et al, 1995 ), and Vitis pseudoreticulata (Lin et al, 2006 ). The expression of APX can be regulated by environmental stimuli, such as salt (Badawi et al, 2004 ), temperature (Kawakami et al, 2002 ), high light (Maruta et al, 2010 ), and heavy metal stresses (Pallavi and Dubey, 2007 ).…”
Section: Introductionmentioning
confidence: 99%